Can governments boost voluntary retirement savings via tax incentives and subsidies? A German case study for low-income households - Giacomo Corneo; Matthias Keese; Carsten Schröder (Kiel University, Department of Economics, 2008)
Since 2002 the German government has promoted private retirement saving plans by means of special subsidies and tax incentives (Riester scheme). This policy mainly targets low-income households. Using data from the German Socio-economic Panel, we scrutinize the impact of the Riester scheme on private savings. Our empirical strategy consists of treating the introduction of the Riester scheme as a natural experiment. The estimation results cast some doubts on the effectiveness of the Riester scheme in raising private savings and call for enhanced systematic efforts to evaluate that policy.
Keywords: D12; I38; H31; H24; D14; 330; retirement saving; Riester scheme; tax incentives; subsidy incentives; pensions; treatment analysis; Private Rentenversicherung; Steuerbegünstigung; Wirtschaftspolitische Wirkungsanalyse; Sparen; Niedrigeinkommen; Deutschland